SMART FARMING SYSTEMS USING INTERNET OF THINGS AND WIRELESS SENSOR NETWORKS - Nana Sujana; Carlos Fernandez (Journal of Computer Science Advancements, 2026)
Agricultural systems increasingly face challenges related to water scarcity, climate variability, resource inefficiency, and growing demands for sustainable food production, creating an urgent need for precise and responsive farming technologies. This study aimed to evaluate the effectiveness of an integrated smart farming system using the Internet of Things (IoT) and Wireless Sensor Networks (WSNs) for environmental monitoring, precision irrigation, resource optimization, and agricultural decision-making. A field-based experimental design was conducted across 24 agricultural plots, comprising 12 IoT–WSN-assisted plots and 12 conventionally managed control plots. Environmental sensors continuously monitored soil moisture, temperature, humidity, and microclimatic conditions, while network and agricultural performance were evaluated using communication reliability, water consumption, response time, and crop productivity indicators. Results showed that IoT–WSN-assisted management reduced irrigation water consumption by approximately 27%, improved soil moisture stability, shortened response times to environmental changes, and increased crop yields compared with conventional management. High packet delivery, network availability, and data completeness supported reliable real-time decision-making. The study concludes that smart farming effectiveness depends on an integrated sensing–communication–processing–decision–action cycle that transforms reliable field data into timely agricultural interventions, offering a scalable framework for improving resource efficiency, productivity, and sustainable agricultural management under increasingly dynamic environmental conditions worldwide.